Efeito do treinamento físico na pressão arterial de adolescentes com obesidade - Farah, Breno Quintella; de Freitas Berenguer, Mariana; do Prado, Wagner Luiz [UNESP]; Crivaldo Gomes, Jr.; Dias, Raphael Mendes R. (FapUNIFESP (SciELO), 2012)
Objective: To systematically review the results of studies that analyzed the effects of physical training on the blood pressure of obese adolescents. Data sources: A systematic review of randomized clinical trials was performed and examined the effect of physical training on the blood pressure of obese adolescents, published in journals indexed at PubMed/Medline, Lilacs, SciELO, and ISI Web of KnowledgeSM databases. Studies that evaluated adolescents published until 2010 and that had a Control Group were included. Data synthesis: Eight studies met the inclusion criteria. Two of them used strength exercises combined with aerobics, while six used only aerobics. Five studies used complementary intervention, especially nutritional. Four studies found decreased systolic blood pressure in the Training Group compared to Controls, together with the reduction in body mass. All studies that found a reduction in systolic blood pressure used aerobic exercises from 12 to 24 weeks three to six times per week, lasting 50 to 90 minutes, and with intensity between 55 and 75% at the maximum heart rate. Conclusions: The effect of physical training on the systolic blood pressure of obese adolescents is controversial. However, the reduction in systolic blood pressure seems to occur with aerobic training programs, that also reduce body mass.
Effect of physical training on the blood pressure of adolescents with obesity
Keywords: Adolescents; Blood pressure; Exercise; Obesity